2014
DOI: 10.1080/14927713.2014.985475
|View full text |Cite
|
Sign up to set email alerts
|

Gendered perspectives of leisure patterns and constraints of university students in Ghana

Abstract: Leisure researchers have contended that leisure patterns and constraints are significantly influenced by gender. Despite this assertion, little has been done to compare gender differences across leisure patterns and constraints within a single study population beyond the treatment of sex as a variable. The focus of this study was to assess the gendered leisure patterns and constraints of university students in Ghana, Africa. Data were collected from randomly sampled students at the University of Cape Coast and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
15
1
1
Order By: Relevance
“…If correct, this could be another explanation for why married and cohabiting women in the current study had a higher probability of being hypertensive. While marriage and its demands can also result in stress in men, the traditionally patriarchal nature of Ghanaian society limits opportunities for stressrelieving leisure activities for women in Ghana and similar sub-Saharan African regions (Henderson, 1996;Adam, 2014). It is still uncommon for women to go out and socialize without their husbands or children in many parts of Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…If correct, this could be another explanation for why married and cohabiting women in the current study had a higher probability of being hypertensive. While marriage and its demands can also result in stress in men, the traditionally patriarchal nature of Ghanaian society limits opportunities for stressrelieving leisure activities for women in Ghana and similar sub-Saharan African regions (Henderson, 1996;Adam, 2014). It is still uncommon for women to go out and socialize without their husbands or children in many parts of Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Article 13 of the Convention on the Elimination of All Forms of Discrimination Against Women reaffirms that women have equal rights to participate and enjoy recreational activities as men. However, studies have shown that there are constraints to women's leisure, and these constraints are cultural, social as well as economic (See; Adam, 2014;Brown et al, 2001;Henderson, 2013;Jackson & Henderson, 1995;Paul, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Women in patriarchal societies can interact with other women inside the boundary of the house, and women often considered it as leisure for them. Gender in leisure studies is a vital variable to the research still, now feminist leisure researchers started to develop theoretical knowledge of leisure and placing feminine leisure as a critical concept to the discussions (Adam, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the prevailing patriarchal arrangements, many Malawian women have more fragmented leisure time than men. Feminist research on leisure studies indicates that the patriarchal organization of society has resulted in notable differences in forms of leisure for men and women, not only in terms of domination of men in leisure spaces but also in the choice of leisure activities (Adam 2014). For example, in their research, Karla Henderson et al (2002) noted that the pattern of leisure activity choice in terms of gender often had females favoring home-based activities while males leaned toward outdoor activities.…”
mentioning
confidence: 99%